Strategi Penerjemahan Onomatope dalam Novel Trilogi The Hunger Games ke dalam Bahasa Indonesia - Syuqaira El Humaira; Hayatul Cholsy (PRASASTI: Journal of Linguistics, 2023)
The use of onomatopoeia in each country often causes problems in the translation process due to differences in culture and background. The socio-cultural conditions of speakers of each language are different so that it also affects onomatopoeic translation. Moreover, translating onomatopoeia in novels becomes a challenge for translators to satisfy readers so that they can understand the content and storyline in the novel. This study aims to analyze the strategies used in onomatopoeic translation in the trilogy novel The Hunger Games by Suzanne Collins which was translated into Indonesian by Desy Rachmaindah. In analyzing the data, the writer uses Baker's (2011) translation strategy. The results of this study indicate that onomatopoeic translation uses 6 translation strategies and some of them use other strategies that are not in accordance with the theory used in the translation novel The Hunger Games and translation strategies using paraphrasing related words dominate because translators tend to translate the source language with the same meaning as the target language.